Perinatal Depression Prevention Through the Mother-Infant Dyad: The Role of Maternal Childhood Maltreatment - Berry, Obianuju O. (J Affect Disord, 2021)
BACKGROUND: Prevention studies for perinatal depression rarely focus on the mother–infant dyad or consider the impact of maternal childhood maltreatment (CM). METHODS: A secondary analysis of two combined randomized controlled trials of Practical Resources for Effective Postpartum Parenting (PREPP) examined the moderating role of CM on the efficacy of preventing perinatal depression and effects on infant behavior at six weeks. RESULTS: 32% of 109 pregnant women endorsed CM (CM+). At six weeks postpartum, women who received PREPP compared to enhanced treatment as usual (ETAU) had significant reductions in depression and anxiety based on the observer-rated Hamilton Rating Scale for Depression (HRSD) and Hamilton Rating Scale for Anxiety (HRSA) (mean difference of M=−3.84 (SD= 0.14, p<0.01) and M=−4.31 (SD= 0.32, p <0.001) respectively). When CM was added to the models, there no longer was a significant PREPP versus ETAU treatment effect on HRSD and HRSA outcomes in CM+ women though effects remained for CM− women. However, CM+ women who received PREPP vs ETAU reported a mean increase in infant daytime sleep of 189.8 minutes (SE= 50.48, p=0.001). LIMITATIONS: Self-report measures of infant behavior were used. CONCLUSIONS: CM+ women versus CM− had limited response to an intervention to prevent perinatal depression yet still reported an increase in infant daytime sleep. This study adds to the growing literature that prevention studies may need to incorporate approaches tailored to fit women with childhood trauma histories while also considering infant functioning as both may be treatment targets relevant to maternal mood.